2014
DOI: 10.1097/bot.0b013e3182a83fdf
|View full text |Cite
|
Sign up to set email alerts
|

Are Bilateral Femoral Fractures No Longer a Marker for Death?

Abstract: Prognostic level III. See instructions for authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…This study is the first to evaluate the cost of conversion THA, although other studies have found an increased complication rate among conversion THAs compared with primary THAs [12–14,25]. Combined with the results of previous studies, the cost differences that we have identified in this study raise the question that conversion THA may be fundamentally different from primary THA.…”
Section: Discussionmentioning
confidence: 61%
“…This study is the first to evaluate the cost of conversion THA, although other studies have found an increased complication rate among conversion THAs compared with primary THAs [12–14,25]. Combined with the results of previous studies, the cost differences that we have identified in this study raise the question that conversion THA may be fundamentally different from primary THA.…”
Section: Discussionmentioning
confidence: 61%
“…Our findings are consistent with previous studies that also found that bilateral femoral shaft fractures are associated with higher morbidity. 2,4,7,16,22 It is well-established that increasing ISS is associated with increased perioperative complications, longer hospital stays, and increased morbidity and mortality, 2,4,[23][24][25] By the nature of its calculation, ISS does not capture the full extent of multiple limb injuries because bilateral and unilateral femur fractures are scored similarly. Therefore, an increase in ISS for this cohort only represents a higher degree of associated injuries.…”
Section: Discussionmentioning
confidence: 99%
“…1 Bilateral femur fractures have been reported to occur in 5%-10% of patients with femur fractures, are associated with a higher mean Injury Severity Score (ISS), increased morbidity, and mortality rates as high as 32%. [2][3][4] Advances in prehospital care and Advanced Trauma Life Support protocols have increased survivorship after highenergy injuries, resulting in surviving patients with higher ISS presentations at trauma centers. 5,6 The care of patients with bilateral femur fractures has added complexity due to the larger physiologic insult associated with increased bleeding, pulmonary complications, longer operative times for management of both femur fractures, and more frequent additional injuries.…”
Section: Introductionmentioning
confidence: 99%
“…Concurrent reaming has only been investigated in bilateral diaphyseal femoral fractures, finding a complication rate of 2% to 7% and mortality of 31.6% and 9.8% with and without associated injuries, respectively. 37,38 However, Giannoudis et al, 39 described an incidence of complications of 4.6%, comparing their series of 14 cases of bilateral diaphyseal femur fractures with 40 unilateral cases, and found that bilateral cases had significantly higher resuscitation requirements, including more blood units transfused, longer duration of intensive care unit and hospital stay, and higher incidence of other injuries than the unilateral cases. Although not significant, the mortality rate of 14.2% was also higher in the bilateral group when compared with 0% in the unilateral group.…”
Section: Type Of Implant and Other Technical Considerationsmentioning
confidence: 99%